2019
DOI: 10.1016/j.foodcont.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural and synthetic antioxidants on changes in 3-MCPD esters and glycidyl ester in palm olein during deep-fat frying

Abstract: The effects of selected antioxidants on the changes of the quality properties and 3monochloropropane-1,2-diol (3-MCPD) esters and glycidyl ester (GE) contents in refined, bleached, and deodorized (RBD) palm olein during the deep-fat frying (at 180 °C) of potato chips were studied. The frying duration was 100 min in five antioxidant systems for three consecutive days. The antioxidants used were butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT), tert-butylhydroquinone (TBHQ), oleoresin rosemary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 20 publications
1
31
1
1
Order By: Relevance
“…A previous study on antioxidant addition to frying palm olein showed that rosemary extract was able to perverse the oil quality in terms of oxidation stability [23]. Similarly, rosemary addition to the shortening was able to give a lower FFA-to-DAG ratio compared to BHA or tocopherol.…”
Section: Oxidation and Stability Of The Fats Portion With Addition Ofmentioning
confidence: 95%
See 2 more Smart Citations
“…A previous study on antioxidant addition to frying palm olein showed that rosemary extract was able to perverse the oil quality in terms of oxidation stability [23]. Similarly, rosemary addition to the shortening was able to give a lower FFA-to-DAG ratio compared to BHA or tocopherol.…”
Section: Oxidation and Stability Of The Fats Portion With Addition Ofmentioning
confidence: 95%
“…There is controversial discussion about the relationship of GE and MCPD esters formation, and therefore the use of antioxidants in reducing GE is still unclear [10]. However, a recent study, concerning the addition of antioxidants to a frying system, had clearly shown that antioxidants were effective in controlling and inhibiting the formation of 3-MCPD ester and GE at the same time [23]. The results showed that GE content was lowered during a series of tests of a continuous frying system with the presence of antioxidants.…”
Section: Mcpd Esters and Ge Formation With The Presence Of Potential mentioning
confidence: 99%
See 1 more Smart Citation
“…These harmful ingredients will be adsorbed on fried foods, and long‐term consumption of such fried foods will cause harm to human health. In recent years, the quality control of frying oil and the safety risk control of the frying process have become a focus for research (Chen, Chiu, Cheng, Hsu, & Kuo, 2013; Wong et al., 2019). TPCs are among those ingredients that are more polar than the triglycerides (TGs) that are produced under frying food conditions (Bansal, Zhou, Barlow, Lo, & Neo, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last five years, thirteen frying bibliography have reported the behaviours of 3-monochloropropane-1,2-diol (3-MCPD) esters and/or glycidyl esters in edible oils, mainly in palm-based oils, when subjected to different frying conditions [8,9,10,11,12,13,14,15,16,17,18,19,20]. Issues associated to 3-MCPD esters and glycidyl esters in refined vegetable oils and fats have gained much attention in the past 10 years considering their potential health implications to humans.…”
Section: Introductionmentioning
confidence: 99%